The role of community resilience as a protective factor in coping with mental disorders in a sample of psychiatric migrants - Olcese, Martina; Madera, Francesco; Cardinali, Paola; Serafini, Gianluca; Migliorini, Laura (Frontiers in Psychiatry, 2024)
Background: Over the past decade in Italy migration to Italy has increased significantly for various reasons including armed conflicts. Generally, tThethe migration process is in general exposeds to different risk factors during different periods of migration, whichthat can compromise well-being and promote the onset or exacerbation of mental disorders. A community with resources and the perception ofperceiving one's community as resilient can be an important protective factor in the context of migration. Purpose: This study aims to understand which variables in migration predict an increase in perceived community resilience and to understand the role of community resilience in the relationship between mental disorders and subjective well-being in a sample of 100 adult migrants at the first consultation interview inat the ambulatories of Psychiatry Unit. Methods: After defining the inclusion and exclusion criteria, migrants were asked to fill out self-report questionnaires to collect socio-demographic data and to assess perception of mental disorders, perceived community resilience and perception of subjective well-being. Descriptive analysis, simple regression, and moderation analyses were conducted to test the hypotheses. Results: The results show that the variable meaning attributed to the community with reference to the host community, migration with someone, and longer durationlength of stay in Italy contribute to increased perceptions of community resilience. In addition, a direct negative effect of mental disorders on subjective well-being and thea moderating role of community resilience in relationship between mental disorders and subjective well-being have been demonstrated. Conclusions: This result underscores the importance of perceived community resilience in mitigating the negative effects of mental disorders on subjective well-being. Perceiving one's community as more resilient seems to protect against the impact of mental disorders on subjective well-being. Our results support an ecological model of migrants' mental health that values the community and its resources in coping with mental disorders in the context of migration.